MATLAB Roadmap to Applications - Chen, Yi; Huang, Long (Springer Nature, 2025)
This open access book presents a comprehensive guide to MATLAB programming, catering to students, engineers, and researchers seeking to harness MATLAB as a powerful tool for their work. The text meticulously covers fundamental concepts, progressing from basic elements such as types and operators to more complex structures like arrays and matrices. It elucidates key programming constructs including selection statements, loop structures, scripts, and functions, providing readers with a solid foundation in MATLAB programming. The book's structure is carefully crafted to facilitate step-by-step learning, with each chapter building upon previous knowledge. Abundant examples and exercises reinforce understanding, while dedicated sections on data visualisation, algorithm development, and practical applications in engineering, science, and finance demonstrate MATLAB's versatility across disciplines. A distinguishing feature of this volume is its inclusion of laboratory work and coursework, allowing readers to apply theoretical concepts to real-world scenarios. This hands-on approach enhances the learning experience and prepares users for practical implementation of MATLAB in their respective fields. In the current era of artificial intelligence, this book serves as an essential resource for those seeking to leverage MATLAB's capabilities. It not only equips readers with programming skills but also illustrates how MATLAB can be integrated into cutting-edge research and industry applications.